Karakteristik Elemen Fisik Sebagai Fasilitas Penunjang Wisata di Kampung Batik Semarang - Yusriya, Azarine Intan; Kurniati, Rina (Teknik PWK (Perencanaan Wilayah Kota), 2024)
Kampung Batik is located in Rejomulyo Village, East Semarang District, Semarang City. Kampung Batik has a strategic location because it is close to leading tourist destinations in the city of Semarang, namely the Old City and the Semarang Old City Museum. The community in Kampung Batik is also a friendly community and has a high spirit to develop Kampung Batik. Although it has potential, the current condition of tourism supporting facilities in Kampung Batik still does not fully meet the needs of tourists. Therefore, identification of the elements of physical design in Kampung Batik is carried out, where these elements are related to tourism amenities / tourism support facilities that are able to meet the needs of tourists. The physical design elements include regional circulation elements, regional signage elements, regional street furniture elements, regional vegetation elements, and elements of regional support facilities. It is known that Kampung Batik has these elements, but not all of the existing elements have good conditions, in accordance with the guidelines, or according to the needs of tourists.